Penerapan RME Berbantuan Canva Untuk Meningkatkan Hasil Belajar Siswa Kelas IV SDN 29 Kota Bengkulu - Zalis, Bella Sonianica; Agusdianita, Neza; Noperman, Feri (JURIDIKDAS, 2024)
This study aims to improve student learning outcomes by applying Realistic Mathematics Education model assisted by canva media. The research instruments were observation sheets and test sheets. Data collection techniques are through observation, testing, and documentation. Data from the results of the first observation were analyzed using descriptive kualitatif. The average results of student activity in cycle I obtained a score of 32.5 with good criteria, which increased in cycle II with a score of 41.5 with very good criteria. Meanwhile test data where analyzed using the formula the average and the percentage of learning completeness. The learning outcomes of students in the knowledge aspect in the first cycle averaged 64.25 with 45% classical learning completeness  and 84.25 in the second cycle with 85% classical learning completeness. The conclusion from this study is that the application of the Realistic Mathematics Education model  assisted by Canva media can improve student learning outcomes.